Association between COL5a1, COL11a1, and COL11a2 gene variations and rotator cuff tendinopathy in young athletes - Alakhdar, Y.; Cook, J.; Gallego, D.; Querol, F.; Chulvi-Medrano, I.; Alberola, A.; Hernández-Sánchez, S. (Clinical Journal of Sport Medicine, 2023)
Objective: Tendinopathy is a prevalent condition in young athletes and in older nonathletic people. Recent tendinopathy research has shown a growing interest in the role played by genetic factors, basically genes involved in collagen synthesis and regulation, in view of collagen disorganization typically present in tendon pathologies.